MANAJEMEN WAKTU DAN JUMLAH PEMBERIAN PAKAN DALAM MENINGKATKAN PERTUMBUHAN DAN SINTASAN IKAN GABUS, Channa striata (Bloch, 1793) - Chatammi Akbar; Deny Sapto Chondro Utomo; Siti Hudaidah; Agus Setyawan (Journal of Aquatropica Asia, 2020)
The nature of cannibalism in snakehead fish (Channa stiata) causes high mortality in snakehead fish farming. Good and proper management is needed to minimize its cannibalism. The aims of this research were intended to find out the feeding frequency and feeding rate in growth performance and survival rate of snakehead fish seed. This research was conducted with Factorial Completely Randomized Design (FCRD), which consisted of 2 factors, feeding rate and feeding frequency each with triplicates. The treatments of feeding rate were 3%, 5%, and 7% and the treatments of feeding frequency were 3 and 4 times everyday. The used feed is commercial feed PF-800. The result of this research indicated that feeding rate 7% with 4 times feeding frequency each day was the highest absolute weight and length of growth rate than the other treatments. The highest value in survival rate parameter was feeding rate 3% with 3 and 4 times/day. On the other hand, the lowest value in FCR parameter was feeding rate 5% with 3 times feeding frequency each day. Meanwhile, the highest value in protein retention parameter was feeding rate 5% with 3 times/day. The result showed that there was any interaction in absolute weight of growth rate and protein retention. The single factor in form of feeding rate gave significant results of survival value and feed conversion ratio. The result of this research showed that feed management of 7% FR with 4 times/day FF gave the best result in growth, FCR, and protein efficiency of snakehead fish. Although, it has the lowest SR value, but 7% FR with 4 times/day FF can produce the highest biomass of snakehead fish in this study reached 114,45g.